Low‐Level Baroclinic Jets Over the New Arctic Ocean. Issue 6 (28th June 2018) - Guest, Peter; Persson, P. Ola G.; Wang, Shouping; Jordan, Mary; Jin, Yi; Blomquist, Byron; Fairall, Christopher
Abstract: During the Sea State cruise in the fall of 2015, in the Chukchi/Beaufort Sea region, there were five strong (>10 m s −1 ) surface wind events associated with low‐level atmospheric jets. These jets were analyzed using rawinsonde observations, ship measurements, and a numerical forecast model. The jets occurred when easterly winds aligned with the ice edge, generating low‐level baroclinicity in a direction favorable for increasing the geostrophic wind speed toward the surface. The maximum wind speed usually occurred at the top of the atmospheric boundary layer with wind speeds greater than 8 m s −1 extending through the capping inversion to 2, 000–3, 000 m elevation, with winds decreasing toward the surface in the boundary layer due to friction. The width (crosswind) dimensions of the jets were 250–400 km and they existed downwind for as long as the winds remained generally parallel to the ice edges, typically several hundred kilometers. Thermal winds calculated from crosswind‐oriented rawinsonde temperature profiles matched the observed vertical wind speed gradients in the inversion regions, indicating that the jets were in quasi‐geostrophic (inversion layer) or quasi‐frictional (boundary layer) balance, with low Rossby numbers. We define these as "baroclinic" type jets, which are distinct from "ice/sea breeze" type jets which flow more down the pressure and density gradients, and have high Rossby numbers. The operational model analyses matched the observations quite well, giving confidence that these types of jets can be simulated and predicted as long as the models have sufficient resolution and accurately parameterize vertical heat fluxes. Plain Language Summary: In recent years, the sea ice that covers the Arctic Ocean has been dramatically decreasing. In places such as the Chukchi and Beaufort Seas (which are northwest and north of Alaska, respectively), there are large areas of open water in the fall season, where 20 years ago there was a thick sea ice cover. When cold Arctic air comes in contact with this relatively warm water, the lower part of the atmosphere heats up. This causes the air to become lighter which decreases the air pressure compared to the air over the remaining sea ice area, which is cold and dense. This contrast in temperature and pressure generates high winds near the surface called "jets." During a recent scientific cruise in the Chukchi and Beaufort seas, the authors launched instrumented weather balloons called rawinsondes which measured temperature, humidity, pressure, and wind profiles during several jet events. These wind events had big impacts on the ocean and ice cover by transmitting momentum to the surface, creating waves, circulations in the upper ocean and destruction of sea ice. These jets, and other phenomena usually associated with more open water, may cause wind speed to increase in the future when there is less sea ice. These jets can be predicted by weather forecast models but present a challenge for global climate prediction models because these climate models do not have a fine enough resolution to accurately simulate the jets. Key Points: Low‐level baroclinic jets in the Arctic are common during cold seasons in ice edge regions due to the horizontal contrast in surface temperature and turbulent heat fluxes During the Sea State cruise all five of the major (>10 m s −1 ) surface wind events were associated with atmospheric jets that had cores near the top of the boundary layer With enough resolution and proper representation of surface conditions, numerical models are able to simulate the jets with good skill